Human herpesvirus-7 as a cause of exanthematous ilnesses in Belém, Pará, Brazil Herpesvírus humano-7 como causa de doença exantemática em Belém, Pará, Brasil - Ronaldo B. Freitas; Maria R. Freitas; Consuelo S. Oliveira; Alexandre C. Linhares (Revista do Instituto de Medicina Tropical de São Paulo, 2004)
We screened sera from 370 patients suffering from exanthematous illnesses in Belém, North Brazil, for the presence of human herpesvirus-7 (HHV-7) IgM and IgG antibodies. Samples were obtained from January 1996 to December 2002 and were processed by a HHV-7-specific indirect immunofluorescence assay (IFA). HHV-7-specific IgM and/or IgG antibodies were found in 190 (51.4%) of these patients, with similar prevalence rates (IgM+ and IgG+ subgroups taken together) for female and male subjects: 52.5% and 50.3%, respectively. Serological status as defined by IgG was identified in 135 (36.5%) patients. In 55 (14.9%) of the patients HHV-7 IgM antibodies were detected. HHV-7 IgM- and- IgG antibody rates were similar (p > 0.05) when male and female subjects are compared: 14.4% versus 15.3% and 38.1% versus 35.0%, respectively. Statistically significant difference (p = 0.003) was noted when HHV-7-IgM-positive female and male patients aged 5-8 months are compared. Prevalence rates ranging from 4.6% (female, 5-8 months of age) to 93.3% (female, > 10 years of age) and 12.2% (male, 5-8 months) to 80.0% (male, 8-10 years of age) were noted in the IgG- positive subgroups. A subgroup (n = 131) of patients with IgM or IgG HHV-7 antibodies were examined for the presence of DNA using a polymerase chain reaction/nested PCR. Recent/active HHV-7 infection occurred at a rate of 11.0% (6/55) among patients whose samples presented IgM+ specific antibodies. In a subgroup (n = 76) of patients with high HHV-7-IgG antibody levels (titre > 1:160) DNA could not be detected in sera examined by PCR/nested PCR. Of the six recent/active infections, four subjects with less than 1 year and two with 3 and 6 years of age, presented typical exanthem subitum (E.S), as defined by higher fever (> 38.0 ºC) with duration of 24 to 72 hours, followed by a maculopapular skin rash. Our results underscore the need for searching HHV-7 infection in patients with exanthematous diseases, particularly those presenting with typical E.S. HHV-7 appears ...